(untitled) - Gear, Jolene (Cambridge, UK, 2002)
The Cambridge Preparation for the TOEFL®Test includes skill-building and practice tests to help learners succeed on the Test of English as a Foreign Language. This comprehensive test-preparation course is ideal for classroom use and self-study. The third edition includes a CD-ROM component containing seven complete practice tests. The tests may be taken in study mode, which generates feedback on their responses, or in test mode, which simulates the experience of taking the exam by computer. The text provides a complete tutorial and a wealth of new activities to introduce students to the new computer formats and activity types. More than 200 exercises fully updated for the new exam, 6 hours of listening material, a complete grammar review, and a mini-writing course are also provided.
Keywords: Tiếng Anh,English language; Kỳ thi,Hướng dẫn học,Examinations,Study guides